KEBIJAKAN ARAB SAUDI MEMUTUSKAN HUBUANGAN DIPLOMATIK DENGAN KANADA - Ririn Widyaprasti; Mohammad Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study intends to analyze Saudi Arabia's Policy to Terminate Diplomatic Relations with Canada. The purpose of this study is to analyze and explain the severance of diplomatic relations by Saudi Arabia against Canada. The crisis of diplomatic relations that is quite serious between Saudi Arabia and Canada is caused by Saudi Arabia's criticism of Canada on human rights. This research is a qualitative research, which is explained based on the existing facts. Behavioral theory helps to analyze the role of non-state actors i.e. Individuals. Other theories used are Foreign Policy Theory, as well as Individual Analysis which helps researchers in finding answers to this research problem. The data collection technique used in this research is library research, in the form of journals, books, official documents, and websites. The results of this study indicate that Canada's criticism of Saudi Arabia on human rights issues caused Saudi Arabia to cut off diplomatic relations with Canada that had existed since 1973. Saudi Arabia's attitude towards this criticism began with a persona non grata statement against the Ambassador's Representative sent by Canada to Saudi Arabia. . On the same day, Saudi Arabia also announced the suspension of all new trade and investment transactions with Canada. This attitude became an introduction to the conflict between Saudi Arabia and Canada.Keywords : Severance of Diplomatic Relations, Saudi Arabia, Canada